Cognitive behavioral therapy in 22q11.2 deletion syndrome: A case study of two young adults with an anxiety disorder. (December 2021) - Buijs, Petra CM; Bassett, Anne S; Gold, David A; Boot, Erik
Background: The prevalence of anxiety disorders is high in 22q11.2 deletion syndrome (22q11.2DS), an under-recognized multisystem condition. Prominent features include an array of somatic, cognitive, and neuropsychiatric disorders. This case study reports for the first time on the application of individual cognitive behavioral therapy in 22q11.2DS. Method: Two young adults with 22q11.2DS and an anxiety disorder received cognitive behavioral therapy based on standard protocols. Feasibility and efficacy were assessed through clinical interviews, clinical observations by the therapist, and questionnaires. Results: Both participants were engaged in the therapy and showed understanding of basic cognitive behavioral therapy principles. However, they did not show a clear clinical improvement. Adjustments to the protocol were required, including increased flexibility and a proactive approach by the therapist, additional time per session, written information, and significant involvement of the family and multidisciplinary team. Conclusions: Our findings may help identify required adaptations to cognitive behavioral therapy protocols for this and similar genetic conditions.